Clinical characteristics of patients having single versus multiple patient encounters within a palliative care programme. Issue 3 (4th February 2016) - Lowe, Sonya S; Nekolaichuk, Cheryl; Ghosh, Sunita; Fainsinger, Lara; Quan, Hue; Fainsinger, Robin
Abstract : Objective: The objective of this study was to describe the clinical characteristics of patient initial presentations, and to explore associations between patients' clinical characteristics at initial presentation and number of encounters (single vs multiple) to an integrated palliative care programme. Methods: This was a retrospective study of a decedent cohort of 2922 patient initial presentations to the Edmonton Zone Palliative Care Program (EZPCP). Data included age, gender, setting of encounter, diagnosis, Edmonton Symptom Assessment System, CAGE, Mini-Mental Status Examination, Palliative Performance Status, Edmonton Classification System for Cancer Pain and time to death. Results: On initial presentation to the EZPCP, the mean age was 73 (SD 14 years), with 1358 (46%) being female, and the majority having a cancer diagnosis (n=2376, 81%), the most common of which was gastrointestinal primary (n=681, 29%). In univariate analyses, patients with younger age (<60), higher palliative performance status (>40%), a malignant diagnosis, gastrointestinal primary or unimpaired cognition at initial presentation were significantly associated with multiple encounters with an integrated palliative care programme (p<0.05). In a multivariate regression analysis, a malignant diagnosis, longer survival, higher performance status and initial entry through acute care sites were independently associated with multiple encounters in the programme (p<0.001). Conclusions: Larger prospective studies are warranted to further elucidate the complex relationships between patient clinical characteristics, initial presentations and subsequent encounters to an integrated palliative care programme.